Emerging Roles for Lymphatics in Chronic Liver Disease - Burchill, Matthew A.; Goldberg, Alyssa R.; Tamburini, Beth A. Jirón (Frontiers in Physiology, 2020)
Chronic liver disease (CLD) is a global health epidemic causing ~2 million deaths annually worldwide. As the incidence of CLD is expected to rise over the next decade, understanding the cellular and molecular mediators of CLD is critical for developing novel therapeutics. Common characteristics of chronic liver disease include steatosis, inflammation and cholesterol accumulation in the liver. While the lymphatic system in the liver has largely been overlooked, the liver lymphatics, as in other organs, are thought to play a critical role in maintaining normal hepatic function by assisting in the removal of protein, cholesterol, and immune infiltrate. Lymphatic growth, permeability and/or hyperplasia in non-liver organs has been demonstrated to be caused by obesity or hypercholesterolemia in humans and animal models. While it is still unclear if changes in permeability occur in liver lymphatics, the lymphatics do expand in number and size in all disease etiologies tested. This is consistent with the lymphatic endothelial cells (LEC) upregulating proliferation specific genes, however other transcriptional changes occur in liver LECs that are dependent on the inflammatory mediators that are specific to the disease etiology. Whether these changes induce lymphatic dysfunction or if they impact liver function has yet to be directly addressed. Here we will review what is known about liver lymphatics in health and disease, what can be learned from recent work on the influence of obesity and hypercholesterolemia on the lymphatics in other organs, changes that occur in LECs in the liver during disease and outstanding questions in the field.